Hubungan Faktor Risiko Penyakit Jantung Koroner dengan Jumlah Lesi Arteri Koroner Berdasarkan Sullivan Vessel Score pada Pasien STEMI - Sarjono, Bezalel T.; Rampengan, Starry H.; Jim, Edmond L. (e-CliniC, 2026)
Abstract: ST-elevation myocardial infarction (STEMI) is a clinical manifestation of coronary heart disease (CHD) with a high mortality rate. The anatomical severity of coronary artery disease (CAD) varies and is influenced by the burden of cardiovascular risk factors. This study aimed to analyze the relationship between CHD risk factors and the number of coronary artery lesions based on the Sullivan Vessel Score in STEMI patients at Prof. Dr. R. D. Kandou General Hospital in Manado. This was an analytical and retrospective study with a cross-sectional design using electronic medical records with total sampling technique. The results showed that among 204 included patients, there were statistically significant relationships (p<0.05) between gender, smoking (38.2%), hypertension (77.5%), dyslipidemia (66.7%), diabetes mellitus (37.3%), and obesity (46.1%) with the number of coronary artery lesions. No statistically significant relationship (p >0.05) was found for the variables of age and family history (2.9%). In conclusion, there is a relationship between gender, smoking, hypertension, dyslipidemia, diabetes mellitus, and obesity with the number of coronary artery lesions, however, there is no relationship with age and family history. Keywords: coronary heart disease; risk factors; coronary artery lesion Abstrak: Infark miokard dengan elevasi segmen ST (STEMI) ialah manifestasi klinis penyakit jantung koroner (PJK) dengan tingkat mortalitas yang tinggi. Derajat keparahan anatomi penyakit arteri koroner bervariasi dan dipengaruhi oleh beban faktor risiko kardiovaskular. Penelitian ini bertujuan untuk menganalisis hubungan antara faktor risiko PJK dan jumlah lesi arteri koroner berdasarkan Sullivan Vessel Score pada pasien STEMI di RSUP Prof. Dr. R. D. Kandou, Manado. Jenis penelitian ialah analitik retrospektif dengan desain potong lintang, menggunakan rekam medis elektronik dengan teknik total sampling. Hasil penelitian mendapatkan bahwa di antara 204 pasien, terdapat hubungan bermakna secara statistik (p<0,05) antara jenis kelamin, merokok (38,2%), hipertensi (77,5%), dislipidemia (66,7%), diabetes melitus (37,3%), dan obesitas (46,1%) dengan jumlah lesi arteri koroner. Tidak ditemukan hubungan bermakna secara statistik (p>0,05) untuk variabel usia dan riwayat keluarga (2,9%). Simpulan penelitian ini ialah terdapat hubungan antara jenis kelamin, merokok, hipertensi, dislipidemia, diabetes melitus, dan obesitas dengan jumlah lesi arteri koroner, namun, tidak terdapat hubungan dengan usia dan riwayat keluarga. Kata kunci: penyakit jantung koroner; faktor risiko; lesi arteri koroner